Estimating Sunda Scop Owl (Otus lempiji horsfield) density based on distance sampling and call playback, Peninsular Malaysia - Pilla, Phillcaine (2016)
Nocturnal birds in the tropics remain little studied primarily due to the logistical difficulties of surveying these birds at night.While call playback has been widely employed in the temperate regions, its practicality has not been adequately demonstrated on tropical owl species.This study aimed to test the feasibility of estimating the density of the Sunda Scops Owl (Otus lempiji) in a lowland forest in Peninsular Malaysia based on distance sampling and call playback.From a total of 58 detections of the owl species from October 2012 to May 2013, 72.41%(42 detections) were made when the birds were breeding. The densities of the owl were estimated at 0.17 ± 0.04 or 0.28 ± 0.06 individuals/ha based on spontaneous and provoked calls (i.e. before and after call playback), respectively. Broadcasting of the calls significantly increased the numbers of detections (χ2 = 16.038, P < 0.001) during both breeding and non-breeding seasons of the birds. Based on logistic regression analysis, the probability of detections was also significantly associated with the owl’s breeding period.The combination of call playback and distance sampling can be potentially applied on other little known and threatened owl species in Southeast Asia.